Current Status and Future Prospects of Treatment for EGFR-Positive Non-Small Cell Lung Cancer After Resistance to EGFR-TKI - Yiming ZENG; Wenfeng FANG; Li ZHANG (Zhongliu Fangzhi Yanjiu)
EGFR-mutant non-small cell lung cancer (NSCLC) is a common type of lung cancer, with EGFR tyrosine kinase inhibitors (EGFR-TKIs) being the standard first-line treatment. However, most patients with NSCLC eventually develop resistance to EGFR-TKIs. Studies on the mechanism underlying EGFR-TKI resistance have driven the development of personalized and precision medicine. Current strategies to address resistance include targeted therapy, immunotherapy, and novel drug treatments. Selecting the appropriate personalized treatment plan is crucial for improving the survival rate and quality of life of patients with EGFR-mutant NSCLC. Thus, this study provides a brief review of the current status and future perspectives in the treatment of EGFR-mutant NSCLC after progression on EGFR-TKI therapy.